Faktor Financial -Non Financial Dan Tingkat Pengungkapan Islamic Social Reporting (ISR) - Anita Anggraini; Mulyaning Wulan (Jurnal Akuntansi dan Keuangan Islam, 2015)
This study examines financial factors namely Size, Profitability and Leverage as wellas non-financial factors, namely Industrial Type and Size of Board of Commissionerthat affect the level of disclosure of ISR. ISR (Islamic Social Reporting) is an index ofsocial responsibility disclosure in accordance with Islamic principles. For users ofcorporate reports that Muslims, disclosure of social responsibility is a form ofaccountability to Allah and is also used as one of the sources of information taken intoconsideration. Therefore, the object of observation in this study is Jakarta IslamicIndex (JII), which is an index that describes Islamic stocks in Indonesia. The results ofthis study demonstrate that the Company Size, Profitability, Leverage, Industry Type,and Size of Board of Commissioners has a significant positive effect on the level ofdisclosure of ISR